2002
DOI: 10.1007/bf02347697
|View full text |Cite
|
Sign up to set email alerts
|

Automatic P-wave analysis of patients prone to atrial fibrillation

Abstract: A method is presented for automatic analysis of the P-wave, based on lead II of a 12-lead standard ECG, in resting conditions during a routine examination for the detection of patients prone to atrial fibrillation (AF), one of the most prevalent arrhythmias. First, the P-wave was delineated, and this was achieved in two steps: the detection of the QRS complexes for ECG segmentation, using a wavelet analysis method, and a hidden Markov model to represent one beat of the signal for P-wave isolation. Then, a set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 16 publications
0
38
0
3
Order By: Relevance
“…Sippensgroenewegen et al have reported the usefulness of spatial analysis using 62-lead QRST subtraction system, 10 and Clavier et al have applied a wavelet analysis on it. 11 Both emphasized the high diagnostic accuracy, but their systems were fairly complicated to apply to routine ECG analysis. There have not been any reported studies that used second derivatives to detect ectopic P waves.…”
Section: Recognition Of Ectopic P Waves In the Differential Diagnosismentioning
confidence: 99%
“…Sippensgroenewegen et al have reported the usefulness of spatial analysis using 62-lead QRST subtraction system, 10 and Clavier et al have applied a wavelet analysis on it. 11 Both emphasized the high diagnostic accuracy, but their systems were fairly complicated to apply to routine ECG analysis. There have not been any reported studies that used second derivatives to detect ectopic P waves.…”
Section: Recognition Of Ectopic P Waves In the Differential Diagnosismentioning
confidence: 99%
“…La Fibrilación Auricular Paroxística (PAF, del inglés Paroxysmal Atrial Fibrillation) es una de las arritmias cardiacas más comunes en la práctica clínica, y aunque no se encuentra asociada a una elevada tasa de mortalidad, son las complicaciones secundarias (por ejemplo tromboembolismos) las que conllevan a un mayor riesgo para el paciente [1][2]. En este contexto, si bien hay muchas formas de estabilizar un ritmo cardiaco afectado por una fibrilación auricular, una posibilidad fiable de pronóstico podría tener un alto interés clínico [3].…”
Section: Introductionunclassified
“…Patrones de este tipo poseen una gran relevancia para el pronóstico de esta patología [1,[13][14]. Sin embargo, la detección de la onda P no es una tarea sencilla y ha sido objeto de diversos trabajos [5].…”
Section: Introductionunclassified
“…When a patient continues with AF as the dominant cardiac rhythm without reversion to the normal rhythm, the condition is known as chronic AF. Two main electrophysiological conditions are indicated for AF initiation and perpetuation [1]: slower conduction velocity in some atrial areas and heterogeneity of cell refractory periods. This heterogeneity of structural and electrophysiological properties leads to a longer and more fragmented P-wave [2][3][4].…”
Section: Introductionmentioning
confidence: 99%